Rb–Sr ages and tectonic setting of some granite intrusions, coastal Labrador - Barton Jr., Jackson M. (Canadian Journal of Earth Sciences, 1977)
Results of Rb–Sr isotopic and chemical analyses from five bodies of granite and from one body of granitic gneiss cropping out along the coast of Labrador between Nain and the Khaumayät (Kaumajet) Mountains are reported. These indicate that: (1) the Okhakh, Nänukhtut, and Saddle Island Granites were intruded between ~2400 Ma ago and ~2300 Ma ago, contemporaneously with the extrusion of volcanic rocks within the Mugford Group; (2) the Loon Granite was emplaced ~1576 Ma ago; and (3) the Operngeviksoakh and Manvers Granites crystallized ~1376 Ma ago and ~ 1280 Ma ago respectively, contemporaneously with the final stages of emplacement of the Nain Complex. These granites are characterized by large initial 87 Sr/ 86 Sr ratios, suggesting that they are of predominantly crystal origin. All of these granite bodies were emplaced post-tectonically and did not accompany any regional deformation or metamorphism.